Predictors associated with readmission in low secure forensic settings in the UK: an exploratory investigation and survival analysis - Harrison, Lauren (The journal of forensic psychiatry & psychology, 2022)
Readmission from secure forensic services has significant implications for individuals and providers. Whilst there is research on readmission for forensic services internationally and for medium secure services in the UK, little is known about rates of readmission to low secure services, and there is no research examining predictors of readmission in low secure services specifically. This study aimed to examine rates and predictors of readmission of 94 individuals discharged from UK-based low secure services.A retrospective quantitative design was employed to assess the rate of readmission. Treatment, demographic, clinical and forensic factors were considered to compare readmitted and non-readmitted groups and examined as possible predictors of readmission.In total, 34% patients were readmitted with an average time to readmission of 524 days. Readmitted patients differed significantly from non-readmitted on prescribed antipsychotic medication, previous forensic admissions, psychology intervention and group psychology intervention. Previous secure forensic admissions, scoring present on HCR-20 historical problems with violence and employability were significantly associated with a shorter time to readmission. Deterioration in mental state was the most common reason for readmission.Time to readmission post-discharge from low secure services can be predicted by several factors that are readily available to clinical teams. This novel exploratory investigation is imperative in furthering understanding of factors associated with readmission to LSFS.